Profil Penderita Covid-19 dengan Komorbid Penyakit Jantung Koroner di Rumah Sakit Umum Haji Surabaya - SHERINA AYU PITALOKA; STEFANUS DJONI HUSODO; RIAMI (HANG TUAH MEDICAL JOURNAL, 2022)
Background : COVID-19 is an illness caused by a new version of corona virus that still has connections with the family of SARS virus. COVID-19 first emerged in Wuhan and spread through contaminated individual contact, droplets, fomites. COVID-19 appear in Indonesia on 2020. Risk factor of COVID-19 exposure is comorbidity like heart disease. Coronary heart disease is a chronical inflammation characterized by the narrowing of coronary artery supplying oxygen. Coronary heart disease as comorbidity, worsens the clinical conditions of COVID-19 patients. Method : This is descriptive research with approach of quantitive method using secondary data. Population are medical records of COVID-19 patients with coronary heart disease comorbid ity in Haji Surabaya Public Hospital on 1st June 2020 to 31st August 2021. Total sampling is used in which all samples are included if in accordance to inclusion criteria in certain periods of time. Variables include age, gender, blood pressure, temperature, BMI, hemoglobin, RBC, WBC, platelet, hematokrit, PPT, aPTT, D-dimer, ECG. Collected data are analyzed descriptively and presented in tables. Results : Research shows COVID-19 patients with coronary heart disease comorbidity profile in Haji Public Hospital Surabaya often happens to age range of 56 – 65 years old, often in man, with normal vital signs. BMI affected fragility of exposure and risk factor of COVID-19 as well as coronary heart disease. CBC shows normal score rate and PPT, APTT majority normal. Abnormality in d-dimer status of patients increased, indicating increase in coagulation activity, abnormality in ECG interpretation shows abnormality of heart functions.